The Effect of Comic Strips towards Students’ Reading Comprehension - Tsania Ranti Purnama; Gatot Subroto; Dewi Murni (Juliet, 2023)
This study aimed to know the effect of comic strips towards students’ reading comprehension at tenth grade students of a Senior High School in Tanjungpinang. The research design in this study was quantitative approach namely pre-experimental research. The participants of this study were a class of tenth grade students in the academic year of 2021/2022. The instruments for collecting the data were reading comprehension test given as pre-test and post-test. The test consisted of 20 questions and the format was multiple choice. The questions made by the researcher according to strategies for reading comprehension and validated by the lecturer and teacher at the target school. The test is given to other class which was similar level to the target class in the same school before given to the experimental class as post-test and pre-test to get the reliability of the test. The results of data analysis revealed that the effect of comic strips towards students’ reading comprehension for tenth grade students was very good. It improved significantly the students’ reading comprehension.